The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/bdr2.1678
|View full text |Cite
|
Sign up to set email alerts
|

Two‐generation reproduction and limited teratology studies of ethanamizuril fed to rats

Abstract: Ethanamizuril, a new anticoccidial agent that belongs to triazine derivatives, has a broad and good anticoccidial activity. To evaluate the reproductive toxicity and teratogenic potential of ethanamizuril, different concentrations of ethanamizuril were administered to Sprague-Dawley rats by feeding diets containing 0, 2, 8, and 30 ppm, respectively. Each group consisting of 30 males and 30 females (F0) was treated with different concentrations of ethanamizuril through a 13-week period before mating and during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In addition, the high dose of toltrazuril caused the weight of the testes and weight of the prostate decreased [13]. However, no obvious body weights, fetal body lengths, tail lengths, litter weights, number of viable fetuse, sexternal, skeletal or visceral malformations in fetuses were noted in any groups in two-generation reproduction and teratogenic test with ethanamizuril, and no adverse effects on the central nervous system, cardiovascular system, and respiratory system were showed in safety pharmacology test either [15,17,18]. Furthermore, the studies of 30 and 90-day subchronic toxicity with feeding ethanamizuril fed to SD rats revealed that the high dose of ethanamizuril, above 60 mg/kg dietary level, could cause minor damage to the liver, kidneys, and other organs, and induce alopecia [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high dose of toltrazuril caused the weight of the testes and weight of the prostate decreased [13]. However, no obvious body weights, fetal body lengths, tail lengths, litter weights, number of viable fetuse, sexternal, skeletal or visceral malformations in fetuses were noted in any groups in two-generation reproduction and teratogenic test with ethanamizuril, and no adverse effects on the central nervous system, cardiovascular system, and respiratory system were showed in safety pharmacology test either [15,17,18]. Furthermore, the studies of 30 and 90-day subchronic toxicity with feeding ethanamizuril fed to SD rats revealed that the high dose of ethanamizuril, above 60 mg/kg dietary level, could cause minor damage to the liver, kidneys, and other organs, and induce alopecia [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high dose of toltrazuril caused the mean weight of the testes and weight of the prostate decreased [13]. However, no obvious body weights, fetal body lengths, tail lengths, litter weights, number of viable fetuse, sexternal, skeletal or visceral malformations in fetuses were noted in any groups in two-generation reproduction and teratogenic test with ethanamizuril, and no adverse effects on the central nervous system, cardiovascular system, and respiratory system were showed in safety pharmacology test too [15,17,18]. Furthermore, the studies of 30 and 90-day subchronic toxicity with feeding ethanamizuril fed to SD rats revealed that the high dose of ethanamizuril, above 60 mg/kg dietary level, could cause minor damage to the liver, kidneys, and other organs, and induce alopecia [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high dose of toltrazuril caused the mean weight of the testes and weight of the prostate decreased [13]. However, no obvious body weights, fetal body lengths, tail lengths, litter weights, number of viable fetuse, sexternal, skeletal or visceral malformations in fetuses were noted in any groups in two-generation reproduction and teratogenic test with ethanamizuril, and no adverse effects on the central nervous system, cardiovascular system, and respiratory system were showed in safety pharmacology test too [15,16,17]. Furthermore, the studies of 30 and 90-day subchronic toxicity with feeding ethanamizuril fed to SD rats revealed that the high dose of ethanamizuril, above 60 mg/kg dietary level, could cause minor damage to the liver, kidneys, and other organs, and induce alopecia [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, a series of toxicity evaluation of ethanamizuril has been carried out in rats and mice, and the NOAEL for the dietary administration of ethanamizuril in the 90-day oral toxicity study for rats was greater than 20 mg/kg. According to VICH's guidelines for repeated dose toxicity tests, the dog is the default non-rodent species which was required in repeat-dose toxicity testing, and the toxicity evaluation in beagle dogs has not been reported [11,12,15,16]. This is unfavourable for understanding the safety and clinical use of ethanamizuril.…”
Section: Introductionmentioning
confidence: 99%